Microwave-Assisted Synthesis of Alginate-Stabilized Gold Nanoparticles - Foliatini, Foliatini; Yulizar, Yoki; Hafizah, Mas Ayu Elita (UI Scholars Hub, 2014)
during boreal summer to fall 2011. In this study, data from satellite observations and atmospheric reanalysis datasets